إمكانية تطبيق معايير المحاسبة الدولية على مؤسسات القطاع العام المندمجة ( دراسة ميدانية على المؤسسة العامة للتجارة الخارجية) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تنبع أهمية دراسة الاندماج من التحديات الكبيرة التي تواجه الاقتصادات المحلية في الوقت الحالي في ضوء المنافسة التي فرضتها السوق الدولية ؛ هذا وتلعب المؤسسة العامة للتجارة الخارجية ( كأحد أهم مؤسسات القطاع العام العاملة في سوريا) دوراً كبيراً في التجارة الدولية فهي تعتبر واجهة القطاع العام الاقتصادي في تعاملاته مع الخارج، ومن هنا تأتي أهمية دراسة العملية  التي تم من خلالها دمج المؤسسات الست المكونة لها للوقوف على المشكلات التي واجهتها بصورة عامة والمحاسبية على وجه الخصوص ، والحد الذي التزمت فيه بمتطلبات معايير المحاسبة الدولية، وبالتالي تقييم قدرة المؤسسة على دخول سوق المنافسة الدولية. وبناء عليه فإن البحث يتناول دراسة الأسس التي تم الاعتماد عليها لإتمام عملية الاندماج والآلية التي تمت بها العملية في ضوء عرض شامل لمعايير المحاسبة الدولية ذات الصلة. The importance of studying merger comes from the huge challenges which face the local economies at present because of competition imposed by international market.  Thus public institution of External Trade (as one of the important institutions working at the public sector in Syria) has an important role at the international trade. It considers the economic public sector at his relations with others outside. Accordingly, the importance of studying the process of merging six institutions consists of following up the whole problems that face it in general and particularly the accounting ones. It also shows the limits that comply with the international accounting standards, and then evaluates the ability of the institution to enter the international competition market. According to this, the research deals with the basics which were relayed on to finish the merging process and its mechanism, in the light of a comprehensive presentation of the related international accounting standards.